Multifunctional nanocarrier systems for effective delivery of drugs in cancer treatment - Mishra B.; Thokala S. (My University, 2025)
The drug delivery to the cancer sites, with maintained effective drug concentration for longer duration, using low dose of drug, with minimum side effects is the prime concern of formulation scientist today. In the recent times, the nanocarrier systems are not only being utilized for achieving targeted, sustained and controlled release of drug to the disease site, but also are used in imaging of diseases. An attempt has been made through this chapter to give a brief outline about the cancer and elaborate details on the various multifunctional nanocarriers researched till date for effective delivery of drugs in cancer treatment. Further, functionalization and surface modification of nanocarrier with various ligands like folate, transferrin, TPGS (d-a- Tocopheryl Polyethylene Glycol 1000 Succinate), trastuzumab and hyaluronic acid etc., that have specific receptor in the proximity of disease site have been explained along with pros and cons of such carrier systems. © 2018, IGI Global. All rights reserved.